One Health strategies for the prevention and control of infections by parasites with zoonotic potential in canines and felines from Quilombola communities in the northeast region of Brazil (Research, Society and Development, 2024)
The objective of this study was to propose One Health strategies for the prevention and control of gastrointestinal parasites (GIP) of canines and felines in six Quilombola communities in the northeast region of Brazil. For this purpose, a field study of a quantitative and qualitative nature was carried out. In canines and felines of both sexes, ages and breeds, fecal samples were collected, and clinical evaluation was carried out. Of the 95 animals, in 54.74% parasites with zoonotic potential were detected: Ancylostoma spp. (96.15%), Strongyloides stercoralis (5.77%), Toxocara canis (3.85%) and Trichuris vulpis (1.92%). Most parasitized animals (61.54%) did not show clinical signs, with a statistical difference in relation to those parasitized with symptoms (p=0.03098). As an unexpected result, 13 individuals with hoarding disorder were identified: 84.61% hoarded animals and 15.38% hoarded animals and objects. Overall, 49.47% were canines from these individuals, in which Ancylostoma spp. (92%) and S. stercoralis (8.0%) were found. The risk of infection was higher for semi-domiciled animals/free access to the street (OR 9.3). This is the first study on GIP in canines and felines from Quilombola communities from Northeastern Brazil, where socioeconomic, health and environmental vulnerability contributes to the risk of parasitism in animals and humans. In the context of One Health approach, a proposal was formulated for the prevention and control of these parasites in canines and felines from these communities, with multi-professional, transdisciplinary and intersectoral actions, respecting the knowledge and culture of Quilombola.